3D morphological variability in foraminifera unravel environmental changes in the Baltic Sea entrance over the last 200 years - Choquel, Constance; Müter, Dirk; Ni, Sha; Pirzamanbein, Behnaz; Charrieau, Laurie M.; Hirose, Kotaro; Seto, Yusuke; Schmiedl, Gerhard; Filipsson, Helena L. (Frontiers in Earth Science, 2023)
Human activities in coastal areas have intensified over the last 200 years, impacting also high-latitude regions such as the Baltic Sea. Benthic foraminifera, protists often with calcite shells (tests), are typically well preserved in marine sediments and known to record past bottom-water conditions. Morphological analyses of marine shells acquired by microcomputed tomography (µCT) have made significant progress toward a better understanding of recent environmental changes. However, limited access to data processing and a lack of guidelines persist when using open-source software adaptable to different microfossil shapes. This study provides a post-data routine to analyze the entire test parameters: average thickness, calcite volume, calcite surface area, number of pores, pore density, and calcite surface area/volume ratio. A case study was used to illustrate this method: 3D time series (i.e., 4D) of Elphidium clavatum specimens recording environmental conditions in the Baltic Sea entrance from the period early industrial (the 1800s) to present-day (the 2010 s). Long-term morphological trends in the foraminiferal record revealed that modern specimens have ∼28% thinner tests and ∼91% more pores than their historic counterparts. However, morphological variability between specimens and the BFAR (specimens cm−2 yr−1) in E. clavatum were not always synchronous. While the BFAR remained unchanged, morphological variability was linked to natural environmental fluctuations in the early industrial period and the consequences of anthropogenic climate change in the 21st century. During the period 1940–2000 s, the variations in BFAR were synchronous with morphological variability, revealing both the effects of the increase in human activities and major hydrographic changes. Finally, our interpretations, based on E. clavatum morphological variations, highlight environmental changes in the Baltic Sea area, supporting those documented by the foraminiferal assemblages.